2022
DOI: 10.1021/acs.bioconjchem.1c00572
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Drug Conjugation on Thermal and Metabolic Stabilities of Aglycosylated and N-Glycosylated Antibodies

Abstract: N-linked glycosylation is one of the most common and complex posttranslational modifications that govern the biological functions and physicochemical properties of therapeutic antibodies. We evaluated thermal and metabolic stabilities of antibody–drug conjugates (ADCs) with payloads attached to the C’E loop in the immunoglobulin G (IgG) Fc CH2 domain, comparing the glycosylated and aglycosylated Fc ADC variants. Our study revealed that introduction of small-molecule drugs into an aglycosylated antibody can com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…No detectable decrease in T m and T agg was observed after MMAE conjugation while, unexpectedly, an increase of T m for approximately 10 °C was found in the human IgG-MMAE ADC. It has been reported that payload conjugation to the IgG CH2 domain could result in either positive and negative effects on T m , depending on the payload properties and the conjugation sites . MMAE molecules have relatively high hydrophobicity and likely adopt an inward orientation in the Fc region to minimize exposure to the hydrophilic surroundings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No detectable decrease in T m and T agg was observed after MMAE conjugation while, unexpectedly, an increase of T m for approximately 10 °C was found in the human IgG-MMAE ADC. It has been reported that payload conjugation to the IgG CH2 domain could result in either positive and negative effects on T m , depending on the payload properties and the conjugation sites . MMAE molecules have relatively high hydrophobicity and likely adopt an inward orientation in the Fc region to minimize exposure to the hydrophilic surroundings.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that payload conjugation to the IgG CH2 domain could result in either positive and negative effects on T m , depending on the payload properties and the conjugation sites. 60 MMAE molecules have relatively high hydrophobicity and likely adopt an inward orientation in the Fc region to minimize exposure to the hydrophilic surroundings. They could form nonpolar interactions with each other or with the hydrophobic IgG residues in the CH2 domain (e.g., F241, F243, V262, V264), which stabilizes the Fc conformation and results in a T m increase.…”
Section: Bioconjugate Chemistrymentioning
confidence: 99%
“…Aglycosylation could be especially advantageous when the priority is to minimize the incidence of liver toxicities and inflammatory responses over enhancing potency. Aglycosylated antibodies can be vulnerable to structural distortion owing to thermal instability; nonetheless, data published in 2022 indicate that attaching small-molecule payloads to the CH 2 domain of the Fc region can compensate for this instability 15 .…”
Section: Review Articlementioning
confidence: 99%
“…It was recently reported that the introduction of small-molecule drugs into Gln of an aglycosylated antibody by using microbial transglutaminase (mTG) can have an impact on the stability of ADC. The hydrophobic cytotoxin was able to compensate for thermal destabilization resulting from structural distortions due to antibody deglycosylation [ 21 ]. The site-specific conjugation of Q295 in deglycosylated antibody was also described by using the same transglutaminase with cystamine for thiolation [ 23 ].…”
Section: Overview Of Site-specific Antibody Conjugationmentioning
confidence: 99%